Organizational stress in high-level field hockey: Examining transactional pathways between stressors, appraisals, coping and performance satisfaction - Didymus, F. F.; Fletcher, D. (International Journal of Sports Science & Coaching, 2017)
This study investigated transactional pathways between organizational stressors and their underpinning situational properties, appraisals, coping, perceived coping effectiveness and performance satisfaction in athletes. Ten high-level field hockey players were interviewed. Data relating to stressors, situational properties, appraisals and coping were analysed using directed content analysis. Mean perceived coping effectiveness scores were calculated and subjective performance satisfaction data were categorized as satisfied, neutral or dissatisfied. A variety of organizational stressors was reported, which were underpinned by five situational properties. Challenge, threat and harm/loss appraisals were experienced and problem solving was the most commonly reported family of coping. High perceived coping effectiveness was not always associated with performance satisfaction. Performance satisfaction was, however, linked to the appraisal experienced. A battery of stress management techniques and ways of coping is useful for optimizing appraisals and alleviating negative outcomes of stress. FROM AUTHOR